A surdez nos jornais do sul do Brasil: uma perspectiva sócio-histórica - Claudio, Débora Pereira (2015)
Currently, we dialogue with discourses published on billboards, newspapers, magazines, television, radio and websites that permeate everyday life, weaving various social voices. In view of this, the objective of this research was to analyze publications of newspapers in southern Brazil that presented directly or indirectly discursive statements produced by deaf people, by other subjects and by the journalist author of the publication about deafness. This research assumed that language is a social activity, and the speeches designed as a dialogic work with social, historical and ideological dimensions. This represents a commitment of this study in contextualize the production of journalistic discoursesas well asthe movement of evaluative meanings constructed in and through language. From the search of digital files of three newspapers in southern Brazildouring the years 2008 to 2010, 177 publications were collected, which were categorized according to state, journal, year of publication andexistence of deaf individualsdiscourses. The category existence of directly or indirectly speaks to a deaf personserved as an exclusion criterion. This way, we analyzed through dialogic discourse analysis, 21 articles that presented deaf people speak, speak of other subjects mentioned in the publication and the journalist speak about deafness. The results showed that when deafness is seen in the publication as missing, as a problem, the solution proposed by the publications is not deaf, but from the outside, through for example the help of an interpreter pounds or surgery in the ear. As part of publicaçõesdetem up failing, others are focused on the possibilities of coming himself deaf, demonstrating how the contradictions of the language of the past and present come out of the mouth of everyday conversation mouth and resurface resignified in newspaper reports. This research, as a counter to the clinical-therapeutic perspective and anthropological deafness, proposes rethinking deafness from a Socio-Historical Perspective, launching a new voice to talk to the speeches of the area and realizing the deaf as unique, historical and social way.